Effects of Astragalus Membranaceus supplementation on oxidative stability of Cashmere goat. Issue 10 (1st September 2020) - Luo, Yulong; Su, Lin; Su, Rina; Wang, Bohui; Liu, Chang; Wang, Zhenggang; Zhao, Lihua; Jin, Ye
Abstract: Astragalus membranaceus (AM) provides a rich source of polysaccharides that can act as powerful antioxidants, but their potential as feed ingredients in the lamb industry still rarely exploited. The objective of this study was to investigate the effect of dietary astragalus membranaceus supplementation on oxidative stability of goat muscles. Longissimus dorsi (LD) muscles from two groups of Cashmere goat (basal diet, C group; basal diet supplemented with 1% astragalus membranaceus root, AM group) were evaluated for lipid oxidation, myoglobin oxidation, activity of antioxidant enzymes, and antioxidant capacity. The results showed that color parameters in Cashmere goat of two feeding conditions were no significant difference ( p > .05). In AM group, myoglobin (Mb) content was higher than C, while metmyoglobin (MMb) ( p < .05) and malondialdehyde (MDA) ( p < .01) were lower. Additionally astragalus membranaceus supplementation had a significant effect on superoxide dismutase (SOD) and catalase (CAT) ( p < .001). In whole, the AM group goats presented a relatively higher antioxidant capacity than C. Especially, RSA and CUPRAC values of AM group goats had significantly higher than C ( p < .05). Consequently, the AM group goats ingested abundant astragalus membranaceus, which enhanced the antioxidant capacity. Thus, it can eliminate free radicals and effectively inhibit oxidation. Abstract : Astragalus membranaceus (AM) provides polysaccharides that can act as powerful antioxidants, and AM goats presented a relatively higher antioxidant capacity than the C (basal diet) goats